2018
DOI: 10.1111/apm.12807
|View full text |Cite
|
Sign up to set email alerts
|

The association of IgA deficiency on infection rate, self‐perceived health, and levels of C‐reactive protein in healthy blood donors

Abstract: The clinical importance of immunoglobulin A (IgA) deficiency in otherwise healthy individuals is not well described. We aimed to investigate the self-reported mental and physical health and the risk of infection in IgA-deficient blood donors compared to healthy control blood donors. Infectious events, recorded in public health registries either as prescriptions filled of any antimicrobial medicine or as hospital infections, were compared between 177 IgA-deficient blood donors and 1770 control blood donors. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
(36 reference statements)
0
3
0
1
Order By: Relevance
“…However, SIgM targeted a broader range of microbes and showed less specificity for microbes compared to SIgA (124). Patients can have increased C reactive protein levels, which is indicative for enhanced inflammation, along with an increased risk of death 10–15 years after initial diagnosis (126, 127). In a recent study no risk association was found between IgA deficiency and hospital infections (127).…”
Section: Iga-associated Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, SIgM targeted a broader range of microbes and showed less specificity for microbes compared to SIgA (124). Patients can have increased C reactive protein levels, which is indicative for enhanced inflammation, along with an increased risk of death 10–15 years after initial diagnosis (126, 127). In a recent study no risk association was found between IgA deficiency and hospital infections (127).…”
Section: Iga-associated Diseasesmentioning
confidence: 99%
“…Patients can have increased C reactive protein levels, which is indicative for enhanced inflammation, along with an increased risk of death 10–15 years after initial diagnosis (126, 127). In a recent study no risk association was found between IgA deficiency and hospital infections (127). IgA deficiency was also not more common among hospitalized individuals compared to healthy blood donors (123).…”
Section: Iga-associated Diseasesmentioning
confidence: 99%
“…Consistent with the previously described anti-inflammatory functions of IgA, many IgA-deficient individuals have an increased incidence of autoimmune disease, recurrent mucosal infections, and an increased incidence of allergy, 38 although others do not seem to suffer from any significant negative health effects. 39 Interestingly, despite the lack of IgA, CD89 remains expressed on cells in these individuals. 40 It is therefore thought that in the absence of mIgA interactions with CD89, anti-inflammatory IgA immune modulation does not occur, thus favoring autoimmunity in the majority of IgA-deficient individuals.…”
Section: Fcari (Cd89): a Bifunctional Regulator Of Iga Responsesmentioning
confidence: 98%
“…Dennoch manifestiert sich die Erkrankung bei 50 % der PatientInnen erst im Erwachsenenalter [35]. Auch im Erwachsenenalter sind die häufigsten PID-Antikörpermangelerkrankungen [36]. Tatsächlich gibt es z.…”
Section: Pid Bei Erwachsenenunclassified